Cooperative Work as a Training Tool for University Students - Daniel Garrote Rojas; Sara Jiménez-Fernández; Nazaret Martínez-Heredia (Universidad Autónoma de Madrid, 2019)
The European Higher Education Area (ehea) proposes to work with active teaching methodologies so that students can reach new competences. Currently, young people must face a changing society influenced by the elimination of borders at the training level and the incorporation of new tools in their formative stage. We have analyzed through cooperative work the development of interpersonal teamwork competence, as a construction of knowledge among equals with similar skills. The rubric is used to analyze how students perceive the development of interpersonal competence through cooperative work. The study was carried out at the University of Castilla-La Mancha on a sample of university students. The obtained results allow to reject the hypothesis of research on differences between the scores of the self-evaluation and the intra-group coevaluation. Statistically significant differences are found in three items, belonging to the first two levels of proficiency, participating and collaborating actively in team activities and contributing to the consolidation and development of the group. In conclusion, we highlight age as a variable associated with better participation by students in the development of the group. Teamwork is important as a methodological tool in the classroom, developing a series of competences within the training and work performance.